2023
DOI: 10.1093/femsre/fuad042
|View full text |Cite
|
Sign up to set email alerts
|

Improving the safety and efficacy of phage therapy from the perspective of phage-mammal interactions

Abstract: Phage therapy has re-emerged as a promising solution for combating antimicrobial-resistant bacterial infections. Increasingly, studies have revealed that phages possess therapeutic potential beyond their antimicrobial properties, including regulating the gut microbiome and maintain intestinal homeostasis, as a novel nanocarrier for targeted drug delivery. However, the complexity and unpredictability of phage behavior during treatment pose a significant challenge in clinical practice. The intricate interactions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…Previous studies have shown that in vivo use of bacteriophages can cause an immune response 63 65 , which may result in a decreased therapeutic efficacy upon repeated administration. For this reason, it was tested whether LUN@RBP P545 and UPSN@CBD SA97 elicited immune responses that could cause any therapeutically undesirable events.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have shown that in vivo use of bacteriophages can cause an immune response 63 65 , which may result in a decreased therapeutic efficacy upon repeated administration. For this reason, it was tested whether LUN@RBP P545 and UPSN@CBD SA97 elicited immune responses that could cause any therapeutically undesirable events.…”
Section: Resultsmentioning
confidence: 99%
“…This study advances our knowledge of the mechanisms by which IAA modulates motility, biofilm formation, bacteriophage sensitivity, and resistance to antimicrobials. Given the role of efflux pumps as virulence factors ( 112 ), as well as the re-emerging potential of phage therapy to combat multidrug-resistant infections ( 113 ), research derived from this work will pave the way for studies aimed at utilizing auxins as anti-virulence agents to combat multidrug-resistant pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…In oral cells, bacteriophages mainly induce anti-inflammatory mediators such as IL-6 and IL1RN to regulate innate and adaptive immunity, thus indirectly affecting cellular signaling and physiological processes [ 31 ]. According to Zou et al, bacteriophages can regulate gene expression, adsorb lipopolysaccharide (LPS), and prevent macrophages from phagocytosing bacteria by activating the pathogen-associated molecular patterns (PAMPs)-pattern recognition receptors (PRRs) pathway [ 32 ]. These discoveries help clarify the intricate interactions between bacteriophages, bacteria, and the oral cavity, as well as the ecological dynamics underlying the rapid evolution of phages.…”
Section: Complex Interactions Between Bacteria Bacteriophages and Ora...mentioning
confidence: 99%
“…It is not the only case; Szafrański et al reviewed the use of bacteriophages and their enzymes to control oral biofilms [ 12 ]. From the perspective of phage-mammalian immune system interactions, Zou et al categorized the factors affecting phage therapy, including the mode of administration and dosage, the physiological state of the patient, and the biological properties of bacteriophages [ 32 ], providing a guide for phage therapy against various human diseases. The next concern is whether bacteriophages mediate adverse effects during therapy.…”
Section: Profiles Of Phage Therapy In Dentistrymentioning
confidence: 99%